2022
DOI: 10.3390/molecules27092983
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of One-Pot Synthesized Fe-MWW Layered Zeolites (MCM-22, MCM-36, and ITQ-2) in Selective Catalytic Reduction of Nitrogen Oxides with Ammonia

Abstract: The application of layered zeolites of MWW topology in environmental catalysis has attracted growing attention in recent years; however, only a few studies have explored their performance in selective catalytic reduction with ammonia (NH3-SCR). Thus, our work describes, for the first time, the one-pot synthesis of Fe-modified NH3-SCR catalysts supported on MCM-22, MCM-36, and ITQ-2. The calculated chemical composition of the materials was Si/Al of 30 and 5 wt.% of Fe. The reported results indicated a correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…Another significant modification of MCM-22P, patented by Corma et al [ 8 ], involves its swelling with centyltrimethylammonium bromide (CTABr), followed by delamination to yield ITQ-2. The structure of the material can be formed using single 2.5 nm-thick MWW layers, organized in a characteristic “house of cards” arrangement [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another significant modification of MCM-22P, patented by Corma et al [ 8 ], involves its swelling with centyltrimethylammonium bromide (CTABr), followed by delamination to yield ITQ-2. The structure of the material can be formed using single 2.5 nm-thick MWW layers, organized in a characteristic “house of cards” arrangement [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rutkowska et al [ 5 ] reported that MCM-36 modified with copper by ion-exchange exhibited almost a 100% NO conversion within 230–530 °C. Moreover, in our previous study [ 9 ], we compared the catalytic performances of one-pot synthesized Fe-MCM-22, Fe-MCM-36, and Fe-ITQ-2. Based on our research, we concluded that Fe-MCM-36 showed the superior potential as the catalyst for NO reduction, especially due to the presence of SiO 2 pillars, which contributed to the formation of new acid centers and towards the well-developed texture of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4, its well-developed pore system, and its thermal stability. According to the Eley-Rideal mechanism, NH 3 -SCR assumes simultaneous adsorption of alkaline NH 3 and neutral NO and their interaction on the catalyst surface [12]. Therefore, high concentration of acid centers delivered by clinoptilolite improves ammonia adsorption capacity and NH 3 -SCR reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…Another important issue in the design of a novel NH 3 -SCR catalyst is the active phase. Over recent years, the focus of researchers has shifted to systems with transition metals, especially iron [5,12,19,20]. The choice of Fe was motivated by its environmentally benign characteristics, low price, and prominent thermal stability.…”
Section: Introductionmentioning
confidence: 99%